The Pre-War Indexes of General Business Conditions - Crum, W. L. (The Review of Economics and Statistics, 1924)
except that cycles (reversed) of reserves of New York Banks are omitted from the present B curve. A revised graphic presentation of the prewar cycles in business is afforded by the chart on pages I94, I95 of the REvIEw for July I923. Chart 2 reproduces the I903-I4 portion of this second, group of curves, and Table 2 gives the corresponding numerical data. The purpose of this note is to compare the summary pictures, of pre-war business conditions, furnished by the old Index Chart and the revised Index Chart. An outline of the compositions of the curves of each index appears in Table 3. In addition to the obvious dependence of each curve in the revised index upon fewer components than the corresponding curve of the old index, it should be remarked that the elimination of secular trend from two components in the revised index rests upon a special statistical device. All twelve components of the old index, and the price of industrial stocks, New York bank clearings, and outside bank clearings, in the re-